Thermal niches and activity periods in syntopic Phymaturus and Liolaemus lizards from the Andes, Argentina - Laspiur, Julio Alejandro (2024)
Explanations for differences in thermal biology within and between species of lizards employ concepts of phylogenetic inertia and plasticity. We compared the thermal biology of three liolaemid species in the Andean highlands in Argentina: two allopatric congeners (Phymaturus williamsi and P. aguanegra) each in syntopy with Liolaemus parvus. We predicted intra and inter-generic differences in ecophysiological traits and periods of activity at both sites, ecotypic differences between the (labile) Liolaemus populations, but predicted no interspecific differences between the (putatively conservative) Phymaturus. We determined the operative temperatures (Te), field body temperatures (Tb), preferred temperatures (Tpref), effectiveness of thermoregulation (E), and activity periods. As expected, P. williamsi differed from L. parvus in Tb, Tpref, and activity periods, likely as result of niche segregation. Contrary to predictions, the Phymaturus populations exhibited differentiation in Tb and Tpref, while L. parvus populations differed in T pref and E. Accordingly, Phymaturus species tend to be effective thermoregulators whereas L. parvus populations behave as good thermoregulators or thermoconformers depending on thermal conditions in fluctuating habitats. Phymaturus may be less evolutionarily conservative than previously suggested. The suite of co-evolving traits affecting thermal ecology may not be collectively conservative nor labile but rather a continuum between both evolutionary paths.